Bernard le Bovier de Fontenelle y Alfons A. Sarasa: una retórica de la felicidad - Sánchez Manzano, María Asunción (2012)
The art of rhetoric provides a large collection of forms to express certain subjects, that rise some kind of debate at the end of seventeenth century. Bernard le Bovier de Fontenelle wrote a brief essay about human happiness, one of the most desirable aims. Our commentary on this treatise is based on a comparison between Fontenelle's and Sarasa's rhetorical report about happiness. In this discussion, Fontenelle was seen to share with Sarasa moral assessment and some key elements. Although these works do not exhaust by any means contemporary theories about happiness, their benefits are able to show the pleasure and profit of ancient tradition, leaving behind Baroque pessimism.
Keywords: Fontenelle, Bernard de, -- 1657-1757; Sarasa, Alfonso Antonio de, -- 1618-1667; Retórica; Felicidad